Mitochondrial uncoupler exerts a synthetic lethal effect against β‐catenin mutant tumor cells. Issue 4 (April 2017) - Shikata, Yuki; Kiga, Masaki; Futamura, Yushi; Aono, Harumi; Inoue, Hiroyuki; Kawada, Manabu; Osada, Hiroyuki; Imoto, Masaya
Abstract : The wingless/int‐1 (Wnt) signal transduction pathway plays a central role in cell proliferation, survival, differentiation and apoptosis. When β‐catenin: a component of the Wnt pathway, is mutated into an active form, cell growth signaling is hyperactive and drives oncogenesis. As β‐catenin is mutated in a wide variety of tumors, including up to 10% of all sporadic colon carcinomas and 20% of hepatocellular carcinomas, it has been considered a promising target for therapeutic interventions. Therefore, we screened an in‐house natural product library for compounds that exhibited synthetic lethality towards β‐catenin mutations and isolated nonactin, an antibiotic mitochondrial uncoupler, as a hit compound. Nonactin, as well as other mitochondrial uncouplers, induced apoptosis selectively in β‐catenin mutated tumor cells. Significant tumor regression was observed in the β‐catenin mutant HCT 116 xenograft model, but not in the β‐catenin wild type A375 xenograft model, in response to daily administration of nonactin in vivo . Furthermore, we found that expression of an active mutant form of β‐catenin induced a decrease in the glycolysis rate. Taken together, our results demonstrate that tumor cells with mutated β‐catenin depend on mitochondrial oxidative phosphorylation for survival. Therefore, they undergo apoptosis in response to mitochondrial dysfunction following the addition of mitochondrial uncouplers, such as nonactin. These results suggest that targeting mitochondria is a potential chemotherapeutic strategy for tumor cells that harbor β‐catenin mutations. Abstract : We screened an in‐house natural product library for compounds that exhibited synthetic lethality towards beta‐catenin mutations and isolated nonactin, an antibiotic mitochondrial uncoupler, as a hit compound. Nonactin, as well as other mitochondrial uncouplers, induced apoptosis selectively in beta‐catenin mutated tumor cells in vitro and in vivo . Furthermore, we found that expression of an active mutant form of beta‐catenin induced a decrease in the glycolysis rate.